Harnessing Vitamin C: Unveiling Its Potential in Cancer Prevention and Treatment - Roy, Antara; Maiti, Dilip K.; Banik, Bimal Krishna (Current Medicinal Chemistry, 2025)
The strong antioxidant vitamin C has been researched for its potential use in the prevention and treatment of cancer. Scavenging free radicals and lowering oxidative stress, which is essential in carcinogenesis, helps to protect cells. Excessive levels of vitamin C can produce hydrogen peroxide and selectively kill cancer cells in the tumor microenvironment by exerting pro-oxidant effects. Normal cells might be spared, indicating a possible window for treatment. Additionally, vitamin C affects important cellular functions that contribute to the development of tumors, including angiogenesis, inflammation, immune response modulation, and epigenetic regulation. Sensitizing tumor cells or shielding healthy tissue from harm caused by treatment may increase the effectiveness of traditional cancer treatments. Recent clinical investigations have revisited the use of high-dose intravenous vitamin C in both monotherapy and combination regimens. While some trials report improvements in quality of life, reduced chemotherapy side effects, and extended survival in specific cancer types, robust evidence of a consistent anticancer effect remains lacking due to variability in study design, cancer type, dosing protocols, and patient populations. Nonetheless, these studies have renewed interest in understanding the pharmacodynamics and clinical utility of vitamin C in oncology. Vitamin C should be considered an investigational approach rather than a standard component of cancer therapy. This review provides a comprehensive overview of the biochemical properties of Vitamin C, its anticancer mechanisms, experimental evidence, clinical data, controversies, and future directions.
Keywords: cancer